Growth promotion of vertical graphene on SiO2/Si by Ar plasma process in plasma-enhanced chemical vapor deposition. Issue 34 (22nd May 2018) - Sui, Yanping; Chen, Zhiying; Zhang, Yanhui; Hu, Shike; Liang, Yijian; Ge, Xiaoming; Li, Jing; Yu, Guanghui; Peng, Songang; Jin, Zhi; Liu, Xinyu
Abstract : This study investigates the growth promotion of vertically oriented graphene in plasma-enhanced chemical vapor deposition through Ar plasma treatment. Abstract : This study investigates the growth promotion of vertically oriented graphene in plasma-enhanced chemical vapor deposition through Ar plasma treatment. Combined with various substrate treatments, including hydrofluoric acid etching and oxidation after Ar plasma treatment, Ar plasma pretreatment promotes vertical growth through the microcavity on the rough substrate surface and the active growth sites. The microcavity affects the strain distribution and defects of as-deposited planar films, which benefit the transition of 2D deposition to 3D vertical growth. A growth model on the effect of Ar plasma pretreatment is proposed.